2019
DOI: 10.1039/c9ta06248c
|View full text |Cite
|
Sign up to set email alerts
|

High performance cation exchange membranes synthesized via in situ emulsion polymerization without organic solvents and corrosive acids

Abstract: This paper demonstrates a new methodology for preparing cation exchange membranes in an effective and environment-friendly way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The first one was the evaporation of water inside the membranes (∼150 °C). The functional groups −SO 3 – in the membranes had a positive retention effect on water molecules, causing the continuous release of water molecules . FT-IR characterization also indicated the existence of water inside CEM-X.…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The first one was the evaporation of water inside the membranes (∼150 °C). The functional groups −SO 3 – in the membranes had a positive retention effect on water molecules, causing the continuous release of water molecules . FT-IR characterization also indicated the existence of water inside CEM-X.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The functional groups −SO 3 − in the membranes had a positive retention effect on water molecules, causing the continuous release of water molecules. 27 FT-IR characterization also indicated the existence of water inside CEM-X. The mass degradation at around ∼380 °C was attributed to the decomposition of −SO 3 − .…”
Section: Membrane Morphology Characterizationmentioning
confidence: 91%
“…73 Ion exchange membranes are produced by incorporating ion exchangers, such as electroactive materials, into a polymer binder. 74 Ion exchange is also widely used in a variety of other industries, including food and beverage production, agriculture, semiconductor manufacturing, power generation, hydrometallurgy, metals finishing, chemical, petrochemical, and pharmaceutical processing, as well as the production of sugar and sweeteners, ground and potable water purification, nuclear reprocessing, and softening. 75 Ion exchangers have a wide range of applications in various fields, including medicine, metal recovery, nuclear industry, water treatment, biotechnology, food production, waste recycling, microelectronics, and more.…”
Section: Membranesmentioning
confidence: 99%
“…To avoid the usage of organic solvents during IEM preparation, relevant researchers have come up with solvent-free strategies. , Xu et al developed a one-pot solvent-free synthesis of cross-linked anion-exchange membranes (AEMs). Jiang and Ladewig proposed a method via in situ emulsion polymerization to synthesize high-performance CEMs without using organic solvents and sulfonation agents. Paul et al reported disulfonated poly­(arylene ether sulfone) desalination membranes formed by solvent-free melt extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…The properties and performance of fabricated CEMs were evaluated in water desalination experiments. 20 14.0 g (67.9 mmol) of sodium SSS was added into a conical flask and completely dissolved in 100 mL of deionized water, followed by the addition of 70.4 mL of tetrabutylammonium hydroxide solution. The liquid was observed to become turbid and was left standing for 30 min at room temperature until the liquid layered.…”
Section: Introductionmentioning
confidence: 99%